2009
DOI: 10.1186/2047-783x-14-9-393
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise training on mobilization and functional activity of blood-derived progenitor cells in patients with acute myocardial infarction

Abstract: Background The aim of the present study was to determine whether regular exercise training (ET) is effective at promoting the mobilization of CPCs and improving their functional activity in patients with recently acquired myocardial infarction(STEMI). Regular physical training has been shown to improve myocardial perfusion and cardiovascular function. This mayberelatedin part to a mobilization of bonemarrow-derived circulating progenitor cells (CPCs) as well as an enhanced vascularisation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…The enhanced expression of endotheliale stickstoffmonoxid-synthase (eNOS) and vascular endothelial growth factor (VEGF) might improve the mobilization of BM-CPCs into the PB and enhance the process of vasculogenesis [46,47]. Moreover, the transient increase in BM-CPCs after regular symptom-limited (ischemic and=or subischemic) exercise training reached a maximum after the regular exercise training for 3 weeks, but did not persist up until 3 months after the regular training [48]. Laufs and colleagues described a significant increase in BM-CPCs after a 4-week, noncontrolled rehabilitation training program in patients with stable coronary artery disease without exercise-induced ischemia [49].…”
Section: Discussionmentioning
confidence: 99%
“…The enhanced expression of endotheliale stickstoffmonoxid-synthase (eNOS) and vascular endothelial growth factor (VEGF) might improve the mobilization of BM-CPCs into the PB and enhance the process of vasculogenesis [46,47]. Moreover, the transient increase in BM-CPCs after regular symptom-limited (ischemic and=or subischemic) exercise training reached a maximum after the regular exercise training for 3 weeks, but did not persist up until 3 months after the regular training [48]. Laufs and colleagues described a significant increase in BM-CPCs after a 4-week, noncontrolled rehabilitation training program in patients with stable coronary artery disease without exercise-induced ischemia [49].…”
Section: Discussionmentioning
confidence: 99%
“…The bone marrow retention of hematopoietic stem cells is critically regulated by stromal cell-derived factor 1a (SDF-1) and its receptor CXCR4 (Peled et al 1999). Studies have shown an upregulation of serum SDF-1/CXCR4 with acute and chronic exercise in healthy volunteers (Okutsu et al 2005), heart failure patients (Sandri et al 2005;Erbs et al 2010), and post-MI patients (Brehm et al 2009), suggesting a role for the SDF-1/CXCR4 axis in exercise-induced BMC retention. Though we did not observe increased abundance of the transcript encoding cell adhesion molecules, we cannot exclude post-transcriptional effects on adhesion molecules and their interactions with injected and/or mobilized BMC's.…”
Section: ; Duranmentioning
confidence: 99%
“…Our previous work has shown that chronic exercise training increases the abundance of cardiac c-kit + cells and Ki67 + cells (Kolwicz et al 2009), consistent with increased regenerative activity. Moreover, other studies have shown that cardiomyocyte proliferation (Bostr€ om et al 2010) and circulating endothelial progenitors increase with training (Rehman et al 2004;Brehm et al 2009). To our knowledge, only one small study has looked at the impact of exercise training on stem cell therapy after MI (Cosmo et al 2012).…”
Section: Introductionmentioning
confidence: 97%
“…Considering the exercise-related activation, mobilization, migratory capacity and homing of blood progenitor cells, and the potential use of these cells as a therapeutic approach in the con-text of CVDs, it can be argued that physical exercise in cardiac rehabilitation programs may enhance the effi cacy of cardiac cellular therapeutic protocols. In fact, Brehm et al [ 23 ] demonstrated that local tissue mechanical and metabolic overload induced by exercise training in a cardiac rehabilitation program enhanced the mobilization of regenerative progenitor cells from bone marrow into peripheral blood, suggesting that this overload may be involved in the regulation of the migratory capacity of blood-derived cardiac progenitor cells. Additionally, authors have verifi ed that exercise-enhanced mobilization and increase migratory capacity of CPCs are associated with improved cardiac function and cardiorespiratory condition in patients with myocardial infarction [ 23 ] .…”
Section: Blood-circulating Progenitor Cells (Cpcs)mentioning
confidence: 99%
“…In fact, Brehm et al [ 23 ] demonstrated that local tissue mechanical and metabolic overload induced by exercise training in a cardiac rehabilitation program enhanced the mobilization of regenerative progenitor cells from bone marrow into peripheral blood, suggesting that this overload may be involved in the regulation of the migratory capacity of blood-derived cardiac progenitor cells. Additionally, authors have verifi ed that exercise-enhanced mobilization and increase migratory capacity of CPCs are associated with improved cardiac function and cardiorespiratory condition in patients with myocardial infarction [ 23 ] . Similarly, exercise training for 3 weeks following AMI resulted in a signifi cant mobilization and increased functional activation of CPCs in humans [ 98 ] , suggesting that regular exercise training may improve the cardiac regenerative capacity after AMI.…”
Section: Blood-circulating Progenitor Cells (Cpcs)mentioning
confidence: 99%